Estabilidad de chicheme procedente del departamento de Córdoba Colombia (2016)
Local products are considered exotic due to their ingredients and the particular production technics; to make them more competitive in the national and international market, conservation strategies that prolong its shelf life must be found. The purpose of this research was to evaluate the chemical, microbiological and sensory stability of “chicheme” prepared traditionally in the municipality of Cienaga del Oro, Cordoba, Colombia. Chicheme was elaborated with the addition of clove Syzygium aromaticum and cinnamon Cinnamomum verumin at concentrations of 730ppm for treatment T1, 1460ppm for T2 and for2190ppm T3 compared with a control. Furthermore, a chemical analysis was performed, determining pH, acidity and °Brix; also a recount of psicrotrofics, total and fecal coliforms, acidic lactic bacteria, Bacillus cereus, Staphylococcus aureus, molds and yeast was carried out. The product was kept in both plastic, PET, and glass jars of 500mL capacity and stored at 4°C for 7 days. The results were subjected to a variance analysis and a Tukey comparison test using the statistical package SAS Windows Version 8. Chicheme added with the highest concentration of cinnamon and cloves and stored in glass containers, showed a longer storage time and a lower count of molds and yeasts. On the other hand, the product placed in plastic containers presented a greater count of microorganisms, probably because PET is more porous than glass.